Reverse transcription-PCR assay for the rapid detection of viable Vibrio cholerae from fresh and processed shrimp - Jeyasekaran, G.; Palanikumar, M.; Varatharajakumar, A.; Jeya Shakila, R. (Indian Journal of Fisheries, 2018)
Viable Vibrio cholerae in seafood was rapidly detected by the Reverse transcription-PCR (RT-PCR) assay developed by targeting mRNA ctxA gene without any pre-enrichment. The PCR product size of the selected gene was 308 bp, which aided in the identification of V. cholerae. This RT-PCR assay was rapid, as it detected V. cholerae from fresh shrimp tissue within 5 min on bio-inoculation when the cell count was 1,000,000 cells. The pathogen was detected in 5 h when the load was 110 cells. The assay even detected the pathogen in shrimp that has been cooked for 10 min, frozen for 30 days and even in dried shrimp. Other food-borne pathogens like Salmonella, Staphylococcus aureus and Listeria monocytogenes were not detected by this assay. The developed RT-PCR assay is thus specific and rapid in detecting the viable Vibrio cholerae in seafood without any pre-enrichment.